Bending properties of stainless steel dynamic compression plates and limited contact dynamic compression plates - Little, F. M.; Hill, C. M.; Kageyama, T.; Conzemius, M. G.; Smith, G. K. (Veterinary and Comparative Orthopaedics and Traumatology, 2001)
The equivalent bending stiffness and bending strength of the stainless steel DCP and stainless steel LC-DCP were compared. Three plates, of each size, were tested destructively in ‘four point bending’. All of the LC-DCP were significantly less stiff and less strong than the comparable size DCP, with the exception of the 4.5 mm narrow LC-DCP which was significantly stronger and more stiff than the 4.5 mm narrow DCP (p <.01). The design advantages of the LC-DCP are ease and versatility of plate application and improved cortical blood flow which one assumes promotes fracture healing. Also, the lower recorded stiffness of the LC-DCP may be advantageous in that it decreases the stress protection of the plated bone. Since optimal strength and stiffness of bone plates are currently unknown, the clinical relevance of the decreased strength and stiffness of the LC-DCP has yet to be determined.Stainless steel LC-DCP and DCP of various sizes were tested in four point bending to ascertain equivalent bending stiffness and bending strength of each type of plate. The LC-DCP were consistently less stiff and strong than their DCP counterparts (p <.01) with the exception of the 4.5 mm Narrow LC-DCP which was stronger and more stiff than the 4.5 mm Narrow DCP. In general, as plate size increased. the difference between the two plate designs decreased. If it can be shown that there is not any detrimental effect on fracture healing, the design features of the LC-DCP make it a desirable choice for most fracture applications.
Keywords: LC-DCP; DCP; stiffness; bending strength; four point bending